1983
DOI: 10.1079/bjn19830068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dietary excess of leucine on the metabolism of tryptophan in the rat: a mechanism for the pellagragenic action of leucine

Abstract: 1. In order to investigate the mechanism of the pellagragenic action of excess dietary leucine, rats were fed on diets providing a minimally-adequate amount of tryptophan, with no preformed niacin, with and without the addition of 15 g leucine/kg diet. This amount of leucine in the diet has been demonstrated previously to lead to depletion of blood and liver nicotinamide nucleotides. The metabolism of tryptophan was assessed by measurement of the production of 14C0, after the administration of [methylene-14C]t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 11 publications
1
50
1
Order By: Relevance
“…Furthermore, it is important to note that when tryptophan is diverted to produce kynurenic acid and quinolic acid, the amino acid is then less available for serotonin synthesis. Only approximately 1% of available tryptophan goes on to metabolize into serotonin, and it has recently been demonstrated that 5‐HT and kynurenine compete for available tryptophan, which leads to serotonin dysfunction during acute stress (Bender, ; Keszthelyi et al, ). However, the complex role of kynurenine is beyond the scope of this review.…”
Section: Serotoninmentioning
confidence: 99%
“…Furthermore, it is important to note that when tryptophan is diverted to produce kynurenic acid and quinolic acid, the amino acid is then less available for serotonin synthesis. Only approximately 1% of available tryptophan goes on to metabolize into serotonin, and it has recently been demonstrated that 5‐HT and kynurenine compete for available tryptophan, which leads to serotonin dysfunction during acute stress (Bender, ; Keszthelyi et al, ). However, the complex role of kynurenine is beyond the scope of this review.…”
Section: Serotoninmentioning
confidence: 99%
“…Measurement of NI--methyl nicotinamide W-Methyl nicotinamide in the incubation medium was determined by the small-scale modification of the alkali-ketone fluorimetric method of Carpenter & Kodicek (1 950) that has been described previously (Bender, 1980). Measurement of methyl pyridone carboxamide Methyl pyridone carboxamide in the incubation medium was determined colorimetrically after removal of interfering substances with MB-5 1 13 mixed-bed ion-exchange resin, hypobromite-catalysed rearrangement to the amine, diazotization, and coupling with napthylethylene diamine, as described previously by Bender (1983), a modification of the methods described by Holman (1954) and Joubert & de Lange (1962).…”
Section: Measurement Of Total Niacinmentioning
confidence: 99%
“…Magboul & Bender (1983) have confirmed that a relative excess of leucine in the diet inhibits the synthesis of NAD(P) from tryptophan in rats. A number of factors may be involved, including: competition between kynurenine and tryptophan for uptake into tissues; increased activity of picolinate carboxylase (Bender, 1983) and inhibition of kynureninase by leucine and of kynurenine hydroxylase by a-oxoisocaproate, the 0x0 acid of leucine (Magbod& Bender, 1983). This last is unlikely to be physiologically important.…”
mentioning
confidence: 99%